Fluorescent carbon dots: rational synthesis, tunable optical properties and analytical applications. Issue 65 (22nd August 2017) - Wang, Yifan; Zhu, Yanwu; Yu, Shaoming; Jiang, Changlong
Abstract : This review summarizes current advances on the design and the employment of fluorescent carbon dots in sensing applications, especially from the point of analytical view. Abstract : Carbon dots (CDs) are a new type of fluorescent carbon nanoparticles (CNPs). In comparison with conventional semiconductor quantum dots and organic dyes, CDs not only have the advantages of non-toxicity and high biocompatibility, but also have excellent water solubility, an adjustable luminous range, high photostability, an absence of light flicker, easy functionality, rich sources of cheap raw materials, easy large-scale syntheses and other excellent characteristics. These excellent properties endow CDs with great potential in many fields, such as environmental monitoring, sensors, catalysis, energy, light-emitting devices, cell markers and biological imaging. With these excellent properties, as well as important applications, CDs have attracted widespread attention in recent years. This article reviews recent progress in CDs in terms of their rational synthesis, tunable optical properties, and analytical applications and put forward the developmental trend of CDs.